Role Ambiguity of School Principals - Tabancali, Erkan; Su, Yasemin (ANI PUBLISHING, 2021)
The present study aimed to find out the school principals' opinions working in public primary and secondary schools concerning their role ambiguity. It is significant for the purpose of this study to set forth the perspectives regarding experiencing the role ambiguity, consider the main factors which lay ground to role ambiguity and prevent situations that may adversely affect the functions of educational organizations in advance. This study employed a qualitative, phenomenological research design. As participants, there were 10 school principals determined with maximum variation sampling. The data, collected with the semi-structured interview, were analyzed and interpreted using the content analysis. The findings obtained in this study revealed two main themes as follows: role ambiguity and influence framework. Role ambiguity was divided into two subthemes as role line and elements of ambiguity. Influence framework'; was divided into four subthemes as organizational ambiguity, pressure groups, ambiguity mirror, and solution paths. The findings obtained in this study showed that school principals experience role ambiguity. It was determined that the role ambiguity of the school principals of this sample resulted from organizational ambiguity and concluded that the school principals determined their roles as per the situation. Within the framework of the results of this study, the factors causing the role ambiguity of school principals should be removed.
Keywords: Ambiguity; role ambiguity; school principals; Education & Educational Research